PENGARUH MEDIA SNADER GAME TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA ANAK USIA 5-6 TAHUN DI TK AISYIAH BUSTANUL ATHFAL V KOTA PEKANBARU - Siti Hajarwan Halimah; Zulkifli N '; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aimed to determine the effect of media Snader Game against Early reading ability in children aged 5-6 years in kindergarten Aisyiah Bustanul RA V Pekanbaru City with methods one group pretest posttest design that experiments conducted on one group alone with no comparison group. As for the total sample of 16 children. Type of instrument used in this study is the observation and documentation using a sheet to record about activities that occurred during a given treatment. Based on the hypothesis test results obtained are the media's influence on the ability to read Snader Game starters in children aged 5-6 years in kindergarten Aisyiah Bustanul RA V of Pekanbaru. Retrieved tcount at 16:59 with sig 0000, because sig <0.05 then we can conclude that there are differences in the ability to know the concept of numbers in a significant protégé before and after use of media images in the learning chain. Hypothesis testing can be seen at t = 16.59> t table = 2, 13145. It has been suggested that there is a significant difference in results between the pretest and posttest. Game Snader media influence on the ability to read beginning at 5-6 years old children in kindergarten Aisyiah Bustanul RA V Pekanbaru City by 49.43%.Keywords: Reading Starters, Media Snader Game